Assessment of Growth and Development in Toddlers: A Mixed Method Approach for Developmental Surveillance and Screening by a Healthy Baby Contest in an Urban Resettlement Colony of Delhi, India - Anita Shankar Acharya; Nidhi Tiwari; Archana Thakur; Sanjeev Kumar Rasania; Damodar Bachani; Jyoti Khandekar (Indian Journal of Medical Specialities)
Introduction: Under-five mortality is still a major concern in India, and we are very far from reaching Millennium Development Goal 4, i.e., reducing child mortality. Various key interventions have been developed to reduce child mortality which needs to be implemented in an integrated manner by our health-care workers. Sole focus of our physicians at primary health-care centers is either clinical management of the child or immunization. In this study, for the overall assessment of the child, a comprehensive healthy baby scorecard has been designed to objectively assess the overall health status of the child and factors affecting it. Methodology: The study was a pilot study designed as healthy baby show contest at an urban health center (UHC) in a resettlement colony of east Delhi. A total of 36 mother–child pairs (children were in the age group of 0–3 years) were enrolled at the UHC for the comprehensive assessment of the child using healthy baby scorecard. Weightage was given to growth which was assessed by three criteria: weight for age, length/height for age, and weight for length/height. In-depth interviews of mothers were conducted to assess their understanding about child development. Results: Overall, 61.1% (n = 22) of participants showed satisfactory nutritional status. Of 14 children with poor nutritional status, 50% of mothers perceived their child to be healthy. Exclusive breastfeeding was present in only 10% of the participants. Correct knowledge about child's normal development was present in 17%–30% of the mothers for various aspects of child rearing. Conclusion: Healthy baby show conducted revealed that child-rearing practices were not conducive for the child's normal development and growth. The main factors are poor knowledge of mother in the concept of child development and child-rearing practices besides other factors such as social and cultural.